212k views
4 votes
-(y-7)=14 solve the following equation

2 Answers

5 votes

First, distribute the negative sign and get -y + 7 = 14

then subtract 7 from both sides and get -y = 7

Divide both sides by -1 and get y = -7

Hope this helps :)

User MultiColourPixel
by
6.1k points
3 votes

Hii!

__________________________________________________________

Answer:

y=-7

Explanation:

First distribute the minus sign.

-(y-7)=14

-y+7=14

Next subtract 7 from both sides.

-y=7

Next, divide both sides by -1

y=-7

--

Hope that this helped! Best wishes.

--

User Juris
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.